Diameter growth performance of tree functional groups in Puerto Rican secondary tropical forests - Adame, Patricia; Brandeis, Thomas J; Uriarte, Maria (Forest Systems, 2014)
Aim of study: Understanding the factors that control tree growth in successional stands is particularly important for quantifying the carbon sequestration potential and timber yield of secondary tropical forests. Understanding the factors that control tree growth in successional stands is particularly important for quantifying the carbon sequestration potential and timber yield of secondary tropical forests. Yet, the high species diversity of mixed tropical forests, including many uncommon species, hinders the development of species-specific diameter growth models. Area of study: In these analyses, we grouped 82 species from secondary forests distributed across 93 permanent plots on the island of Puerto Rico. Material and Methods: Species were classified according to regeneration strategy and adult height into six functional groups. This classification allowed us to develop a robust diameter growth model using growth data collected from 1980-1990. We used mixed linear model regression to analyze tree diameter growth as a function of individual tree characteristics, stand structure, functional group and site factors. Main results: The proportion of variance in diameter growth explained by the model was 15.1%, ranging from 7.9 to 21.7%. Diameter at breast height, stem density and functional group were the most important predictors of tree growth in Puerto Rican secondary forest. Site factors such as soil and topography failed to predict diameter growth. Keywords: Caribbean forests; growth model; tropical forest succession; Puerto Rico.